Determinants of Indonesia’s Economic Growth 2010 – 2022 (Indonesia Panel data Analysis Using ARDL) - Budiarty, Ida; Sitorus, Nurbeti Herlina (Pt. Anagata Sembagi Education, 2024)
Economic growth is one of the main indicators in measuring the welfare of a country. So the conditions of economic growth are very important for a country, the higher the economic growth of a country, the better the welfare of its people. This paper examines the effect of the number of labor force employed and the Gross Fixed Capital Formation (PMTB) on economic growth. Research data is secondary data, which is a combination of time series and cross-section data. By using cross-section data from 34 provinces in Indonesia with a period of years from 2010 to 2022. Panel Autoregressive Distributed Lag (ARDL) method is used to identify the long-run and short-run relationship between independent and dependent variables. The results of this study indicate that the number of employed labor force has a positive and significant effect on economic growth in the long run, but has a negative and significant effect on economic growth in the short run. Meanwhile, Gross Fixed Capital Formation has a positive and significant effect on economic growth in both the long and short run.